Sudden bilateral sensorineural hearing loss in a patient immunocompromised by the human immunodeficiency virus - Castro,Rafael Freire de (2018)
Abstract It is known that in less than a third of patients presenting sudden hearing loss, the disorder can be attributed to viral infection, trauma, neoplasms, and vascular and autoimmune diseases. However, the role of the HIV in the onset of this disease has not yet been well described. A 46-year-old female, in an immunosuppression state induced by HIV infection, presented with sudden bilateral hearing loss, with no improvement despite treatment. Several mechanisms were reported by which the virus could induce damage to the auditory pathway. However, little is known regarding the prevention and treatment of this morbidity.